Differences in Quality of Female Nursing Work Life Based on Gender and Nursing Perspectives - Dodi Wijaya; Kholid Rosyidi Muhammad Nur; Nurfika Asmaningrum; Dinda Rizky Amalia (KHD-Production, 2023)
The quality of a nurse’s work life is the degree of satisfaction regarding personal and organizational needs based on experience in a work organization. A nurse with a dual role is the nurse who acts as a mother and a professional nursing staff at the same time. The purpose was to determine differences in the quality of female nurses’ work life in gender and nursing perspective at Balung General Hospital and Kalisat General Hospital in Jember Regency. The research method uses a comparative study with a quantitative research type. The sampling technique in this research is random sampling with a total of 115 samples. Data collection was conducted by using questionnaires about the quality of nurses’ work life from the nursing perspective and questionnaires conflict with women’s dual role from the gender perspective. Data processing using the Mann-Whitney analysis test with a 95% significance level (α=0.05). The results using Mann-Whitney analysis showed that there is a difference between the gender perspective and the nursing perspective (p=0.000). The mean results showed that the nursing perspective () is higher than the gender perspective (). The conclusion shows that the quality of female nursing work life from the gender perspective needs to be improved. The hospital needed to review further regarding work schedules and shift time; the family needed to provide full support and good cooperation; and female nurses themselves must also have good coping control, time, and energy management. Apart from that, it is necessary to have a policy from the room head and team leader regarding the distribution of schedules for female nursing staff without reducing the feeling of unfairness for male health workers.